Anti-inflammatory effects of oroxylin A on RAW 264.7 mouse macrophages induced with polyinosinic-polycytidylic acid - LEE, JI YOUNG (Exp Ther Med, 2016)
Oroxylin A (5,7-dihydroxy-6-methoxy-2-phenylchromen-4-one; Baicalein 6-methyl ether) is an active flavonoid compound originally isolated from Scutellaria radix, which has been used to treat pulmonary infection in Korea, China, and Japan. Oroxylin A is known to possess dopamine reuptake inhibitor activity. However, the effects of oroxylin A on virus-induced macrophages has not been fully elucidated. In the present study, the anti-inflammatory effects of oroxylin A on double-stranded RNA-induced macrophages were examined. Production of nitric oxide (NO), various cytokines, as well as calcium release and the mRNA expression of signal transducer and activator of transcription 1 (STAT1) in dsRNA polyinosinic-polycytidylic acid (PIC)-induced RAW 264.7 mouse macrophages were evaluated. Oroxylin A restored the cell viability in PIC-induced RAW 264.7 mouse macrophages at concentrations of up to 50 µM. Additionally, oroxylin A significantly inhibited the production of nitric oxide (NO), interleukin (IL)-1α, IL-1β, IL-6, IL-10, interferon gamma-induced protein 10, granulocyte-colony stimulating factor (CSF), granulocyte macrophage-CSF, leukemia inhibitory factor (IL-6 class cytokine), lipopolysaccharide-induced CXC chemokine (LIX), monocyte chemoattractant protein 1, macrophage inflammatory protein (MIP)-1α, MIP-1β, MIP-2, Regulated on Activation, Normal T Expressed and Secreted, tumor necrosis factor-α, and vascular endothelial growth factor as well as calcium release and the mRNA expression of STAT1 in PIC-induced RAW 264.7 cells (P<0.05). Thus, the present results suggest that oroxylin A has anti-inflammatory properties, associated with its inhibition of NO, cytokines, chemokines and growth factors in PIC-induced macrophages via the calcium-STAT pathway.